Stellar flares - Adam F. Kowalski (Living Reviews in Solar Physics)
Abstract Magnetic storms on stars manifest as remarkable, randomly occurring changes of the luminosity over durations that are tiny in comparison to the normal evolution of stars. These stellar flares are bursts of electromagnetic radiation from X-ray to radio wavelengths, and they occur on most stars with outer convection zones. They are analogous to the events on the Sun known as solar flares, which impact our everyday life and modern technological society. Stellar flares, however, can attain much greater energies than those on the Sun. Despite this, we think that these phenomena are rather similar in origin to solar flares, which result from a catastrophic conversion of latent magnetic field energy into atmospheric heating within a region that is relatively small in comparison to normal stellar sizes. We review the last several decades of stellar flare research. We summarize multi-wavelength observational results and the associated thermal and nonthermal processes in flaring stellar atmospheres. Static and hydrodynamic models are reviewed with an emphasis on recent progress in radiation-hydrodynamics and the physical diagnostics in flare spectra. Thanks to their effects on the space weather of exoplanetary systems (and thus in our search for life elsewhere in the universe) and their preponderance in Kepler mission data, white-light stellar flares have re-emerged in the last decade as a widely-impactful area of study within astrophysics. Yet, there is still much we do not understand, both empirically and theoretically, about the spectrum of flare radiation, its origin, and its time evolution. We conclude with several big-picture questions that are fundamental in our pursuit toward a greater understanding of these enigmatic stellar phenomena and, by extension, those on the Sun.